Perjanjian Perkawinan Ditinjau Dari Kitab Undang-undang Hukum Perdata Pasal 29 Undang-undang Perkawinan Nomor 1 Tahun 1974 - Fatmasari, Fatmasari (Fakultas Hukum Universitas Kanjuruhan Malang, 2014)
In accordance with human nature has an instinct and desire to maintain or off spring generation. In this case, something makes it happen is do weddings or marriage. Marriage is the only way to form a family, because marriage is absolutely necessary as a requirement of establishment a family also according to any religion. Therefore, the authors formulate the issues in the following questions: (1) what forms of marriage Agreement in the Book of the Law and the Civil Law No.1 of 1974AboutMarriage? (2). How legal consequences arising from the implementation of the Agreement in the Book of Marriage of Law and the Civil Law Act No.1 of 1974? The research method used in this paper is the normative law research methods that the research done by examining library material so secondary data consisting of primary legal materials, law materials and secondary law materials tertiary. The problems marital agreement forms and legal consequences in the Civil Code and Marriage Act No. 1 of 1974: (a) In the Article 29 of the Marriage Law No.1 of 1974 is simpler and stronger because it must be made in writing not to say like what is prescribed in Islamic law. Where the marriage agreement made by both sides in writing can also be made in the form of certificates and approved by the Registrar of Marriage Employees are held. In Article 29 paragraph (1) of the Marriage Law No.1 of 1974 has been determined that the agreement must be in writing form. (b) The legal consequences arising under Law no.1In 1974, the sides must also be prepared with the legal consequences that would arise if the violation of the marriage agreement. Morally and psychologically marriage agreement would lead to a feeling of distrust towards his life partner. He will be shadowed by the fear if their partner violated the agreement. This anxiety will lead to unhappiness in running the household. In sociological and cultural marriage agreement caused the existence culture shock